Chemical and fatty acids composition of fish roes - M. Vasconi; F. Bellagamba; V.M. Moretti (Taylor & Francis Group : Università degli studi di Milano, 2017)
The global crisis of wild caviar production, due to the block of catch quotas granted by the CITES, caused by the steady decline of world sturgeon populations and the limited production from aquaculture, that has not made up for the caviar demand, has allowed the creation of a market for cheap caviar substitutes. Various fish species are used for the production of caviar substitutes, whose eggs shows different characteristics from a nutritional point of view. The aim of present study was to investigate the chemical composition and fatty acid profile of fish roes deriving from seven different species, collected in the Italian market. The survey involved 12 samples of salmon eggs (Oncorhynchus keta), 11 of lumpfish (Cyclopterus lumpus), 3 of rainbow trout (Oncorhynchus mykiss), 3 of pike (Esox lucius), 3 of cod (Gadus morhua), 3 of Alaska pollock (Theragra chalcogramma) and 3 of capelin (Mallotus villosus). The eggs proximate composition (AOAC standard methods) and fatty acid profile (GC analysis) were determined. The data were processed by SPSS 22 statistical package. Salmon eggs (217.3 ±32.7 mg) were the biggest while the smallest resulted the cod eggs (0.16 ±0.08 mg). Generally, eggs of greater size showed the higher protein and lipid content. Protein content ranged from the value of 29.6 ±0.8 g/100g of salmon to the 8.1 ±0.6 of capelin, while lipid content ranged from 12.8±0.6 of salmon to 2.8 ±0.6 of Alaska pollock. With regard to the fatty acid composition, the fish eggs showed some peculiarities. EPA and DHA (their sum ranged from 46.6% of total fatty acid of pollock to the 20.9% of pike) were dominant in all sea species (salmon, capelin, cod, pollock and lumpfish) while pike and trout presented a higher amount of oleic acid (21.6 % and 27.1% respectively). Eggs from trout, the only farmed species, presented also a significant amount of linoleic acid (9.4%) if compared with all the other species. This content probably derived from the vegetable oils utilized in feed formulation. This study contributes to ...